Evaluation of causal sentences in automated summaries - Puente, C.; Villa Monte, Augusto; Lanzarini, Laura Cristina; Sobrino, A.; Olivas Varela, José Angel (2017)
This paper presents an experiment to show the importance of causal sentences in summaries. Presumably, causal sentences hold relevant information and thus summaries should contain them. We perform an experiment to refute or validate this hypothesis. We have selected 28 medical documents to extract and analyze causal and conditional sentences from medical texts. Once retrieved, classic metrics are used to determine the relevance of the causal content among all the sentences in the document and, so, to evaluate if they are important enough to make a better summary. Finally, a comparison table to explore the results is showed and some conclusions are outlined.
Formato de archivo PDF. -- Este documento es producción intelectual de la Facultad de Informática - UNLP (Colección BIPA/Biblioteca)
IEEE International Conference on Fuzzy Systems (2017 : Nápoles, Italia)
Keywords: SOFT COMPUTING; resúmenes automáticos